2019
DOI: 10.14295/bds.2019.v22i1.1673
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cone Beam Computed Tomography to Identify the Morphology of Maxillary and Mandibular Premolars in Chennai Population

Abstract: Objective: The complex root canal anatomy is inherently colonised by microbial flora. Endodontic treatment success is always related to adequate disinfection of the root canal space, which ultimately affects the treatment outcome. A thorough understanding of the external and internal root canal anatomy by using adequately imaging modalities is essential before planning any treatment. The aim of this study was to investigate the number and morphology of the root canals of maxillary and mandibular premolars in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Comparative gender difference studies are summarized in Table 2 . A higher [ 15 , 22 , 24 , 33 , 36 , 47 ] or similar [ 2 ] frequency of the 1–1–1/1 RCC in female individuals has been reported. A second root in Mn2Ps has been also reported [ 2 , 3 , 6 , 7 , 10 , 11 , 14 , 20 23 , 29 , 33 , 34 , 38 , 39 , 41 , 47 ] with a frequency from 0.1 to 8.0% (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Comparative gender difference studies are summarized in Table 2 . A higher [ 15 , 22 , 24 , 33 , 36 , 47 ] or similar [ 2 ] frequency of the 1–1–1/1 RCC in female individuals has been reported. A second root in Mn2Ps has been also reported [ 2 , 3 , 6 , 7 , 10 , 11 , 14 , 20 23 , 29 , 33 , 34 , 38 , 39 , 41 , 47 ] with a frequency from 0.1 to 8.0% (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The results are divided into authors, year and reference number, population, number of teeth investigated, research method employed, root canal configuration frequency (%) and number of roots (%) (Table 1 ). It could be observed that most of the investigated Mn2Ps were single-rooted (89.5–100%) [ 2 , 3 , 6 , 7 , 10 , 11 , 14 16 , 18 , 20 24 , 27 29 , 31 – 35 , 37 39 , 41 , 42 , 46 , 47 ], followed by two-rooted Mn2Ps with a frequency lower than 8% [ 2 , 3 , 6 , 7 , 10 , 11 , 14 , 20 23 , 29 , 33 , 34 , 38 , 39 , 41 , 46 , 47 ], while three roots were reported only in 0.1 to 3.5% [ 2 , 7 , 33 ]. A 1–1–1/1 RCC is the most frequently observed classification in Mn2Ps (Vertucci’s and Weine’s Type I) with a frequency up to 99.6% [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations